Multiantigenic subunitary vaccines against tuberculosis in clinical trials: Where do we stand and where do we need to go?. Issue 5 (3rd May 2016) - Guapillo, Carolina; Hernández-Pando, Rogelio; Flores-Valdez, Mario Alberto
ABSTRACT: The idea of presenting this commentary is to bring attention to the current status of clinical tests from several multiantigen vaccine candidates based on proteins produced by means of genetic engineering and molecular biology approaches and to suggest how new emerging technologies (OMICs) and bioinformatics might benefit vaccine development for better control of tuberculosis.